Supplementation of amino acids to prevent reperfusion injury after liver surgery and transplantation: where do we stand today? - Hoffmann, Katrin; Büchler, Markus W.; Schemmer, Peter (Clinical nutrition, 2011)
Background & aims - Functional liver failure remains one of the major complications after liver surgery. Ischemia/reperfusion injury (IRI) is strongly associated with increased morbidity and mortality after liver resection and transplantation. An ischemia induced activation of Kupffer cells with subsequent release of toxic mediators leads to disturbance of intrahepatic microcirculation, increased oxygen consumption of the liver and depletion of hepatic glycogen reserves. Aim of this review was to summarize the evidence for prevention of IRI by amino acid supplement and to give an overview on potential clinical use in liver surgery. - Methods - A systematic literature search (Medline, Embase, and The Cochrane Central Register of Controlled Trials) was performed to identify the relevant literature. - Results - Amino acid supplement has hepatoprotective effects and is non-toxic. Up to now heterogenic results have been reported from clinical trials. However, positive effects on microcirculation, leukoycte-endothelial interaction, Kupffer cells and pro-inflammatory mediator release have been described in trials investigating glycine supplementation. The data for N-acetylcysteine remain heterogenic. - Conclusion - An effective protection against IRI by amino acid supplementation has been demonstrated in experimental and several clinical studies. However, further clinical trials are warranted to identify the most promising approach for a routine clinical application.
Gesehen am 29.07.2022